(untitled) (Eurasian Research Bulletin, 2022)
The article analyzes the design sequence in the process of creating a new model of clothing: choosing a topic, developing a concept, studying source materials, creating drawings. Also, the development of specific stages in the future transformation of new types of modern clothing in the study of an artistic source, presents procedures for maintaining an imaginary connection with the original source.